USE OF NEW INFORMATION TECHNOLOGIES IN STUDENTS’ STUDYING OF ENGLISH LANGUAGE - Spivakovska Є.О. (Journal of Information Technologies in Education (ITE), 2013)
Particular use of new information technologies in teaching of future teachers of foreign languages; didactic possibilities of information technologies in teaching English language are described in the article.